PEMBELAJARAN SAINS FISIKA MELALUI PENDEKATAN SETS (SCIENCE ENVIRONMENT TECHNOLOGY SOCIETY ) PADA SISWA KELAS VIII MTs NURUL FALAH AIR MOLEK - Mitri Irianti; Zulirfan Zulirfan; Arifah Zaini (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
The purpose of this research was to find the result of sains physic achievement through approach ofSETS. The subject of the research was students of class VIII of MTs Nurul Falah Air Molek the sample takenwas 44 students. The instrument of collecting data was test of learning achievement research is about resultof student and product evaluation sheet. Data wil be analyze by using describe analyze with includesabortive power, learning effectiveness, completeness of student’s study and completeness of learns purpose.The result of data analysis shows average of student’s abortive power is 74, 8% with good’s category,completeness of student’s study and completeness of learns purpose with complete category. However,approach of SETS effective enough of student learning for learning of sains physic to camera and periscopematerial.Key words: approach of SETS, sains physic learning